Learn to program Visual Basic - Smiley, John
Professor John Smiley answers 100 questions he's most commonly asked by beginning and intermediate programmers in "Learn to Program Visual Basic Examples." This book includes a unique interactive format, provides practical applications for programmers, and details solutions that are diffucult to find in help files and standard documentation. This book is thought-provoking reading for all Visual Basic programmers -- not just in answering problems, but also introducing some neat techniques you may never have thought of for giving your programs real power